Emergent TandemHeart-ECMO for acute severe mitral regurgitation with cardiogenic shock and hypoxaemia: a case series. Issue 1 (6th January 2020) - DiVita, Michael; Visveswaran, Gautam K; Makam, Kasaiah; Naji, Peyman; Cohen, Marc; Kapoor, Saurabh; Saunders, Craig R; Zucker, Mark J
Abstract: Background : Acute severe mitral regurgitation (MR) associated with cardiogenic shock is a life-threatening emergency. Traditional teaching has focused on the need for emergent coronary angiography and/or intra-aortic balloon counterpulsation in preparation for emergent open-heart surgery for repair/replacement. Unfortunately, emergent open-heart surgery in patients with acute MR complicated by cardiogenic shock is associated with 25–46% perioperative mortality. New devices have provided additional options for stabilization prior to emergent surgery which facilitate improved outcomes. Case summary : We present two cases of acute severe MR resulting in cardiogenic shock and profound hypoxaemia. TandemHeart ® mechanical circulatory support with an oxygenator spliced into the circuit, akin to veno-arterial extracorporeal membrane oxygenation (ECMO), facilitated haemodynamic stabilization and decongestion of the lungs facilitating successful bridge to mitral valve surgery. Successful discharge to home was achieved in both patients with good neurological outcomes and sustained long-term functional recovery at 18 and 14 months, respectively. Discussion: Selective use of the TandemHeart ®, with or without ECMO, facilitates management of the critically ill cardiogenic shock patient with acute severe MR.